Poly(High Internal Phase Emulsion) of 2-EHA, 2-EHMA and EGDA with naturally occurring phenolic compounds", paper presented at international conference on ?polymers for advanced technology - Ingavle, Ganesh C.; Shaikh, A. A.; Bhongale, Sunil Sitaram; Scaria, S.; Chavan, Nayaku; Qureshi, Mohammed; Ponrathnam, Surendra (Polymers for Advanced Technology, 2006)

Transfer of technology (ToT) document of polyimide binder resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan. N. N.; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhansekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (2009)

Amino functionalized oligoimides telechelics - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Reddy, Krishna Mohan Srinivasulu; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Deokar, Sarika Babasaheb; Mulani, Khudbudin Baban; Ghorpade, Ravindra V.; Bhongale, Sunil Sitaram; et al. (2010)
This invention relates to a process for the preparation of amino functionalized oligoimide telechelics. More particularly it relates to a process for the preparation of soluble oligoimide prepolymers which can be used as matrix resins that can be rapidly cured to form stable polyimides with amino end functionalities. The amino functionalized oligoimide telechelics are suitable for conversion into three dimensional polymeric systems through condensation chemistry such as reaction with oligo epoxies (epoxy-imide resins), polyacids (polyamide imides) and polyhalogenated compounds (poly amine - imides) to form crosslinked structures having enhanced thermal stability and mechanical strength. The polymers prepared by the process of this invention can be used as materials in advanced composites having high temperature stability.

Determination of organic acid impurities in lactic acid obtained by fermentation of sugarcane juice - Qureshi, Mohd Shadbar; Bhongale, Sunil Sitaram; Thorave, Archana K. (Journal of Chromatography A, 2011)
Lactic acid produced by fermentation process mostly contains a number of aliphatic carboxylic acids as impurities. In this work, carboxylic acid impurities in lactic acid samples from a number of sources were determined at ppm levels. A simple HPLC method was developed that utilized a new generation polar embedded reverse phase, 20 mM phosphate buffer at pH 2.20 (+/- 0.05) and UV detection at 210 nm. The method enabled quantitative analysis of the above acids in lactic acid matrix. The experimental conditions for column temperature, mobile phase pH and flow rate were optimized. A detailed validation of the method was performed for linearity, precision, accuracy, selectivity, limit of detection (LOD), limit of quantitation (LOQ), ruggedness and repeatability and reproducibility (R&R). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Lactic acid; Method validation; Organic acid impurities; Polar embedded RP-HPLC; Sugarcane juice fermentation

Transfer of technology (ToT) document of ethyl silicate-32 - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of Technology (ToT)/ Technical Documents, 2011)

Transfer of technology (ToT) document of phenol-aniline-formaldehyde (sf-342a) resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of technology (ToT) document, 2011)

Amino functionalized oligo polyimides with enhanced storage stability - Dwivedi, Mayank; Rao, Locanindi Hari Sarvothama; Mohan, Srinivasulu Reddy Krishna; Dhanasekharan, Janakiraman; Rao, Bevara Madhusudana; Kumar, Sriperambudur Rajesh; Ponrathnam, Surendra; Rajan, Chelanattukizhakkemadath Raman; Tayal, Rajiv Kumar; Shadbar, Qureshi Mohammed; Chavan, Nayaku; Deokar, Sarika Babasaheb; et al. (WO2012090055A1, 2012)
The invention relates to an improved process for the preparation of amino functionalized oligomeric monomeric reactant type polyimides having higher stability. More particularly it relates to a process for the preparation of soluble imide prepolymers, used as matrix resins that can be rapidly cured with multi-functional moieties such as diepoxy, dicarboxyl, anhydride, diisocyanates to form crosslinked structures having enhanced thermal stability and mechanical strength.

Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.

Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate - Harikrishna, Reghunathan; Shaikh, A. W.; Ponrathnam, S.; Rajan, C. R.; Bhongale, Sunil Sitaram (Designed Monomers and Polymers, 2014)
Photopolymerization of high internal phase emulsions based on 2-ethylhexyl (meth)acrylates and ethylene glycol dimethacrylate was carried out in presence of low concentration of different photoinitiators. The stable emulsions obtained by mixing with individual photoinitiators were subjected to low-intensity photopolymerization under UV-Visible lamp. Identical samples were irradiated for differing periods ranging from 2 to 10min at an interval of 2min. The percentage conversions of each monomer in the compositions with respect to the time of irradiation were determined using gas chromatography. It was observed that the formulations containing IRGACURE 819 showed the highest conversion while that containing IRGACURE 2959 showed the least conversion. The former showed high conversion due to the proximity of the absorption maxima of photoinitiator to the major emission line of mercury spectrum at 365nm while the latter showed least conversion due to non-availability of major absorption maxima within the irradiation range.
Keywords: (meth)acrylates; high internal phase emulsion; Photopolymerization; residual monomer analysis

Ambient temperature photocopolymerization of tetrahydrofurfuryl methacrylate and isobornyl methacrylate: reactivity ratios and thermal studies - Rajdeo, K. S.; Ponrathnam, S.; Pardeshi, S.; Chavan, Nayaku; Bhongale, Sunil Sitaram; Harikrishna, Reghunathan (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2015)
Photocopolymerization of heterocyclic monomer namely, tetrahydrofurfuryl methacrylate with bulky bicyclic monomer, isobornyl methacrylate with different feed ratios was carried out in bulk with low concentration of an -hydroxyl ketone based photoinitiator. The ambient temperature photocopolymerization was carried out by using a UV-Visible lamp with fixed low intensity of 0.4mW cm(-2) for a period of 6min. The residual monomer remained in the polymerization process were determined by using gas chromatography. The reactivity ratio values for the two monomers were calculated from the copolymer composition data by using Fineman-Ross, Kelen-Tudos, Extended Kelen-Tudos and Mao-Huglin methods. Individually, as well as the average of all the methods revealed that the monomer reactivity ratios of tetrahydrofurfuryl methacrylate were higher than isobornyl methacrylate. The dyad sequence distribution and dyad sequence lengths were calculated using the Igarashi and Pyun method and the sequence length distribution for tetrahydrofurfuryl methacrylate was observed to be higher with an increase in its feed content. This supports the reactivity ratio studies that a higher monomer reactivity ratio value for tetrahydrofurfuryl methacrylate was observed as compared to its comonomer. The thermal studies showed that the glass transition temperatures of the copolymers increased with an increase in isobornyl methacrylate content.
Keywords: Copolymer; methacrylates; micro structure; photocopolymerization; reactivity ratios; thermal studies